2009
DOI: 10.1590/s1415-47572009005000107
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 antitrypsin gene polymorphism in Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Alpha-1-antitrypsin (AAT) plays an important role in the pathogenesis of emphysema, the pathological lesion underlying the majority of the manifestations of Chronic Obstructive Pulmonary Disease (COPD). In this study we tested the hypothesis that common AAT polymorphisms influence the risk of developing COPDs. We investigated PiM1 (Ala213Val), PiM2 (Arg101His), PiM3 (Glu376Asp), PiS (Glu264Val) and PiZ (Glu342Lys) SERPINA1 alleles in 100 COPD patients and 200 healthy controls. No significant differences were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Eleven SNPs of the genes encoding IL‐10 and the alpha subunit of its receptor (IL10RA) were not associated with the rate of decline in FEV1 in smoking‐induced COPD . Carriers of tested polymorphisms (PIM1, PIM2, PIM3, PIS and PIZ) of Alpha‐1 antitrypsin gene were not associated with the annual decline of FEV1 determined for 2 years in a Tunisian study .…”
Section: Gene Polymorphisms and Lung Function Declinementioning
confidence: 93%
See 2 more Smart Citations
“…Eleven SNPs of the genes encoding IL‐10 and the alpha subunit of its receptor (IL10RA) were not associated with the rate of decline in FEV1 in smoking‐induced COPD . Carriers of tested polymorphisms (PIM1, PIM2, PIM3, PIS and PIZ) of Alpha‐1 antitrypsin gene were not associated with the annual decline of FEV1 determined for 2 years in a Tunisian study .…”
Section: Gene Polymorphisms and Lung Function Declinementioning
confidence: 93%
“…A meta‐analysis including 16 case–control studies and cross‐sectional studies demonstrated that patients with PI MZ had higher risk to suffer from COPD as compared with those with PI MM homozygotes , while another meta‐analysis found that individuals with PI SZ heterozygotes had significantly higher risk for COPD . Another study on SERPINA1 alleles of M1, PI M2, PI M3, PI S and PI Z found no significant differences in allele frequencies between COPD patients and healthy controls . Further studies are needed with enough cases to confirm the role of those gene homozygotes in the risk of COPD.…”
Section: Gene Polymorphisms and Copd Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…DNA samples with the Pi∗M were cut into 78- and 20-bp bands, but the Pi∗S remained as a 98-bp band. While for the Z-variant (Pi∗MZ, Pi∗ZZ), the previously described Hyp99I/amplified fragment length polymorphism (AFLP) method was adopted [31]. Exon V was amplified using the primer pair (IDT DNA) 5M (5′-GAGCCTTGCTCGAGGCCTGGGATC-3′), and 5P (5′-CAGGAAAACATGGGAGGGATTTAC-′3).…”
Section: Methodsmentioning
confidence: 99%
“…A null mutation of SERPINA1 gene was shown to significantly increase the risk of severe emphysema 2. Single nucleotide polymorphisms (SNPs) of SERPINA1 have also linked to a heightened susceptibility to COPD 3,4. However, majority of these studies were performed in Caucasians, definitive evidence of such an association is yet to be demonstrated in Asian population 5,6…”
Section: Introductionmentioning
confidence: 99%